Angola - Seabra, P.; Martins, V. (The handbook of African defence and armed forces, 2025)
After more than three decades of internal strife and extensive involvement from key international actors, Angola’s oversized military apparatus found itself without a core mission following the end of hostilities in 2002. Since then, the Angolan Armed Forces (FAA) have been used interchangeably as means of national reconciliation, internal repression, and external power projection. However, these roles have been adopted with varying degrees of priority and effectiveness. This chapter explores the ensuing adaptation of the FAA as dictated by a lingering wartime legacy, the aftermath of multiple disarmament, demobilization, and reintegration (DDR) processes, and the atomization of authority for the protection of the state. The combined effect of these three elements helps to explain the set of capabilities made available, the functional overlapping of internal structures of the state, and the fleeting interest in meeting broader African security demands.